Feasibility and safety of hyperthermic intraperitoneal chemotherapy using 5‐fluorouracil combined with cisplatin and mitomycin C in patients undergoing gastrectomy for advanced gastric cancer. Issue 8 (25th July 2017) - Murata, Satoshi; Yamamoto, Hiroshi; Naitoh, Hiroyuki; Yamaguchi, Tsuyoshi; Kaida, Sachiko; Shimizu, Tomoharu; Shiomi, Hisanori; Naka, Shigeyuki; Tani, Tohru; Tani, Masaji
Abstract : Background and Objectives: We conducted a dose‐finding study for 5‐fluorouracil (5‐FU) administered with cisplatin (CDDP) and mitomycin C (MMC) to find an improved regimen for hyperthermic intraperitoneal chemotherapy (HIPEC) for advanced gastric cancer (GC). Methods: The appropriate HIPEC regimen previously determined in vitro was 5‐FU (200 µg/mL), MMC (2 µg/mL), and CDDP (10 µg/mL) at hyperthermic conditions (42°C) for 30 min. This was a clinical study to determine the recommended dose of 5‐FU in combination with MMC and CDDP at 42°C for 30 min and to evaluate HIPEC safety in patients at high risk of developing peritoneal metastases following GC surgery. Results: Twelve patients were treated with surgery plus HIPEC using 5‐FU at 0, 500, 750, and 1000 mg combined with MMC (10 mg) and CDDP (50 mg) in the perfusate (5 L). Dose‐limiting toxicities did not develop until 1000 mg 5‐FU was reached. Four patients experienced grade 1 or 2 adverse events. The recommended dose was 1000 mg 5‐FU/5 L perfusate. Eight (66.7%) patients demonstrated no recurrence of peritoneal metastases; 5‐year overall survival rate was 83.3%. Conclusion: Gastrectomy and HIPEC with MMC, CDDP, and 5‐FU is feasible, safe, and may protect against peritoneal metastasis following surgery for advanced GC.